A highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material and its preparation method
By adopting a high-dispersed coated Co3O4/MoS2/CC heterostructure in the electrolytic water-based hydrogen production electrode material, the problem of high cost of precious metal electrode materials is solved, and efficient and stable electrochemical hydrogen evolution catalytic performance is achieved, which is suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202211421829.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-14
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-11-14
AI Technical Summary
The existing electrolytic water-based hydrogen production electrode materials mainly rely on precious metal Pt/Ir, and the raw material reserves are low and the cost is high, which limits its large-scale industrial application.
Using a highly dispersed coated Co3O4/MoS2/CC heterostructure hydrogen evolution electrode material, a porous structure covered with nitrogen doped carbon is formed by in situ by generating cobalt-based MOFs on a three-dimensional conductive carbon cloth and converting them into a Co3O4/MoS2 heterostructure.
Good electrochemical hydrogen evolution catalytic performance and stability are achieved, and the overpotential to reach the current density of 10mA·cm-2 is only 86.1mV, and the Tafel slope is 104.4mV·dec-1, which is suitable for large-scale production.
Smart Images

Figure CN115717251B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of hydrogen energy, and in particular relates to a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material and a preparation method thereof. Background Art
[0002] With the progress of the times and the rapid development of the economy, the frequent production activities of human beings have brought about a series of problems such as over-exploitation of fossil fuels and environmental deterioration, which greatly limit the progress of human civilization and the improvement of the quality of life. Therefore, finding, developing and utilizing new clean energy has become the research focus of various scientific researchers. Although the total amount of sustainable clean energy resources such as ocean energy, solar energy, and wind energy is large and pollution-free, their large-scale development and utilization are limited by the difficulty of direct utilization and the discontinuity of supply. Therefore, in order to efficiently enrich, transform and utilize these energy forms, the design and research of energy conversion devices are crucial. Hydrogen energy, as a new type of clean energy, has the advantages of high calorific value, renewability, single product (H2O) and no pollution, and is expected to become a perfect substitute for fossil fuels. The preparation methods of hydrogen mainly include hydrogen production from fossil fuels, hydrogen production from biomass, and hydrogen production from light / electrolysis of water. Among them, water electrolysis is one of the most promising key technologies for achieving renewable utilization of hydrogen energy. The earth is rich in water resources, and the electricity converted from renewable energy or the oversupply of electricity in the power grid can be used to electrolyze water to produce hydrogen, achieving low-cost, clean, and efficient conversion of hydrogen energy and peak-valley balance of electricity. However, the current electrode materials for water electrolysis are mainly based on precious metals (Pt / Ir) and their compounds, with low raw material reserves and high costs, which limits its large-scale industrial production and application. Therefore, the development of a non-precious metal-based, simple-to-process and highly stable hydrogen evolution catalyst is still one of the important directions for the current application of water electrolysis to produce hydrogen.
[0003] Transition metal-based composites have made rapid progress in the electrocatalytic decomposition of water in recent years. Electrochemical hydrogen evolution electrodes based on transition metal compounds and their heterogeneous composite structures have shown good electrocatalytic activity and stability. Among them, molybdenum disulfide has attracted widespread attention as a hydrogen evolution electrocatalyst due to its good conductivity and electrochemical activity. However, the electrocatalytic active sites of molybdenum disulfide crystals are only distributed at the edges and defects of the sheets, and often face the problem of low density of effective catalytic active sites. Therefore, it is necessary to prepare molybdenum disulfide-based composites with rich defects and small grain size through appropriate structural regulation to achieve better electrocatalytic hydrogen evolution activity. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, the primary purpose of the present invention is to provide a method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material. The catalytic electrode material prepared by this method has good electrohydrogen evolution activity and catalytic stability, the material preparation operation is simple, the micro-nano structure is controllable, and it is easy to industrialize.
[0005] Another object of the present invention is to provide a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material prepared by the above method.
[0006] The purpose of the present invention is achieved through the following solutions:
[0007] A highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material comprises the following steps:
[0008] (1) Cut the conductive carbon cloth into a certain shape (the size of the carbon cloth can be adjusted according to the size of the reactor), soak it in an alcohol solution and remove organic impurities on the surface by ultrasound, take it out and rinse it with water, then soak it in a potassium permanganate solution at room temperature, take it out and wash and dry it;
[0009] (2) 2-methylimidazole is stirred and dissolved in water to form a solution A; cobalt nitrate hexahydrate is stirred and dissolved in water to form a solution B; after solutions A and B are completely dissolved, solution B is poured into solution A, and the mixture is mixed and stirred evenly, and the carbon cloth dried in step (1) is placed flat in the mixed solution and soaked at a constant temperature; the carbon cloth is taken out, washed, and dried to obtain a carbon cloth loaded with cobalt-based MOF, which is referred to as Co-MOF;
[0010] (3) immersing the Co-MOF obtained in step (2) in a sodium molybdate dihydrate aqueous solution at a constant temperature, taking it out and washing it with water to remove the unstable substances on the surface, and drying it at 50° C. for 12 h to obtain CoMoO4 / CC;
[0011] (4) Place the CoMoO4 / CC prepared in step (3) flatly in a porcelain boat with a lid, place 90 mg of thiourea in the direction of the air inlet, and place the CoMoO4 / CC in the direction of the air outlet. Perform a constant temperature heat treatment in an Ar gas environment, and the sample obtained by sulfurization is recorded as Co3O4 / MoS2 / CC.
[0012] The alcohol solution in step (1) is any one of ethanol and isopropanol, preferably 95% ethanol;
[0013] The mass molar concentration of the potassium permanganate solution in step (1) is 0.5M, and the immersion time is 1-2h;
[0014] The molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate in step (2) is 8:1;
[0015] The constant temperature soaking in step (2) refers to soaking at 25° C. for 6-8 hours;
[0016] In steps (1) to (3), the washing refers to rinsing with deionized water, and the drying refers to drying at 50° C. for 6-12 hours;
[0017] The concentration of the sodium molybdate dihydrate aqueous solution in step (3) is 2-10 mg / mL; the constant temperature immersion refers to immersion at 25° C. for 12-24 hours;
[0018] In step (4), the Ar gas flow is preferably 50 sccm;
[0019] The constant temperature heat treatment in step (4) refers to heating to 500°C and constant temperature heat treatment at 500°C for 1-2h, with a heating rate of 2-5°C·min -1 ;
[0020] A highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material prepared by the above method.
[0021] The inventive mechanism of the present invention:
[0022] Using three-dimensional conductive carbon cloth (CC) as a substrate, a cobalt-based MOF is generated in situ on its surface and further converted into a nitrogen-doped carbon-coated Co3O4 / MoS2 heterostructure, which constructs an excellent electron transfer pathway, abundant catalytic active sites and a stable carbon-based armor for the electrode material, thereby achieving an improvement in its electron transfer efficiency and intrinsic catalytic activity. At the same time, the electron migration efficiency and stability of the electrode material are also key indicators that affect the efficiency and economy of electrocatalysis. Therefore, the present invention directly designs and in situ prepares heterogeneous nanostructures with abundant electrochemical active centers on a conductive substrate to realize its application in the field of electrocatalytic hydrogen evolution, which is of great significance.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] (1) A highly dispersed coated Co3O4 / MoS2 / CC heterostructure self-supporting hydrogen evolution electrode material prepared by the present invention is used for electrocatalytic hydrogen evolution. A three-dimensional carbon cloth is used as a growth substrate. After cobalt-based MOF nanocones are dip-coated with sodium molybdate dihydrate ions, an in-situ sulfurization heat treatment is performed to obtain a highly dispersed, nitrogen-doped carbon-coated Co3O4 / MoS2 nanoparticle heterostructure, and the porous nanocone structure is retained. Furthermore, when the highly dispersed coated Co3O4 / MoS2 / CC heterostructure self-supporting electrode material prepared by the present invention is used for acidic electrocatalytic hydrogen evolution reaction, it reaches 10 mA cm -2 The overpotential of the current density is only 86.1mV, and the Tafel slope is 104.4mV·dec-1 , and has good electrochemical hydrogen evolution catalytic performance and stability.
[0025] (2) The highly dispersed carbon-coated Co3O4 / MoS2 / CC heterostructure self-supporting hydrogen evolution electrode material prepared by the method of the present invention is a highly dispersed porous structure formed by nitrogen-doped carbon-coated Co3O4 / MoS2 heterostructure nanoparticles. It not only has the characteristics of high conductivity and high stability of carbon materials, but also the wrapped Co3O4 / MoS2 heterostructure has excellent hydrogen evolution performance. The highly dispersed heterogeneous nanoparticles and the nitrogen-doped carbon coating layer are beneficial to the charge transfer and the exposure of active sites.
[0026] (3) The highly dispersed carbon-coated Co3O4 / MoS2 / CC heterostructure self-supporting hydrogen evolution electrode material prepared by the method of the present invention has a multi-level porous structure constructed by Co3O4 / MoS2 heterostructure nanoparticles and nitrogen-doped carbon coating layers. The nanoparticles closely connected with the nitrogen-doped carbon are conducive to electron transfer and electrocatalytic stability, and the porous structure can increase the contact area between the electrode material and the electrolyte. The highly dispersed nanoparticle structure can obtain more interface defects and active sites, enhance the intrinsic activity of the material, and thus obtain high electrochemical hydrogen evolution performance. The surface nitrogen-doped carbon coating structure can obtain excellent electron transfer efficiency and electrochemical stability, and can maintain stable performance during long-term hydrogen evolution reactions.
[0027] (4) The present invention adopts a method combining room temperature reaction and hydrothermal synthesis, which is simple to operate, low in cost, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD pattern of Co3O4 / MoS2 / CC sample prepared by the present invention;
[0029] Figure 2 The SEM image of the Co3O4 / MoS2 / CC sample prepared by the present invention; the left image is a SEM image magnified 5000 times, and the right image is a SEM image magnified 40000 times;
[0030] Figure 3 LSV curve of the electrochemical hydrogen evolution process of the Co3O4 / MoS2 / CC sample prepared by the present invention;
[0031] Figure 4 The Tafel slope of the electrochemical hydrogen evolution process of the Co3O4 / MoS2 / CC sample prepared in the present invention;
[0032] Figure 5 This is the long cycle stability curve of the Co3O4 / MoS2 / CC sample prepared in the present invention. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0035] Example 1
[0036] (1) Cut the conductive carbon cloth into a shape of 3*2 cm, soak it in 95% ethanol for 15 min to remove organic impurities on the surface, and then rinse it with deionized water; then soak it in 30 mL 0.5 M potassium permanganate solution at room temperature for 1 h to improve the surface hydrophilicity, and then rinse it with deionized water after taking it out, and dry it at 50°C for 6 h;
[0037] (2) 2-Methylimidazole (1313.6 mg) was stirred and dissolved in 40 mL of deionized water to form a solution A; cobalt nitrate hexahydrate (582.06 mg) was stirred and dissolved in 40 mL of deionized water to form a solution B; after solutions A and B were completely dissolved, solution B was poured into solution A, and the mixture was mixed and stirred for 5 min to obtain a uniform solution; the carbon cloth dried in step (1) was placed flat in the mixed solution and soaked at a constant temperature of 25° C. for 6 h; the carbon cloth was taken out, washed with deionized water, and dried at 50° C. for 12 h to obtain a cobalt-based MOF-loaded carbon cloth, which was recorded as Co-MOF;
[0038] (3) Sodium molybdate dihydrate (0.1 g) was stirred and dissolved in 35 mL of water, and the Co-MOF obtained in step (4) was immersed in the solution for ion exchange, and immersed at a constant temperature of 25° C. for 12 h; after taking out the immersed sample, the surface-loaded unstable substances were rinsed with deionized water, and dried at 50° C. for 12 h to obtain CoMoO4 / CC;
[0039] (4) Place the CoMoO4 / CC prepared in step (3) flat in a porcelain boat with a lid, place 90 mg of thiourea in the direction of the air inlet, and place the CoMoO4 / CC in the direction of the air outlet. Heat the Ar gas environment (gas rate 50 sccm) to 500 °C (heating rate 5 °C min -1 ), and heat treated at 500℃ for 1h, the sulfurized sample was recorded as Co3O4 / MoS2 / CC.
[0040] The highly dispersed coated Co3O4 / MoS2 / CC heterostructure self-supporting hydrogen evolution electrode material prepared by the present invention can reach 10 mA·cm when used for acidic hydrogen evolution reaction. -2 The overpotential of the current density is only 86.1mV, and the Tafel slope is 104.4mV·dec -1, and has good electrochemical hydrogen evolution catalytic performance and stability.
[0041] Figure 1 The XRD diagram of the Co3O4 / MoS2 / CC sample prepared in the present invention shows that the sample exhibits characteristic peaks of both Co3O4 and MoS2 crystals, proving the successful preparation of the material.
[0042] from Figure 2 It can be seen from the SEM image of the Co3O4 / MoS2 / CC sample prepared by the present invention that the present invention uses three-dimensional carbon cloth as the growth substrate, obtains N-doped porous carbon through in-situ carbonization and ion exchange of cobalt-based MOF nanocones, and then in-situ generates a MoS2 coating layer with a nanosheet interlaced structure on its surface to form a multi-level porous structure.
[0043] Figure 3 and Figure 4 The LSV curve and Tafel slope of the electrochemical hydrogen evolution process of the Co3O4 / MoS2 / CC sample prepared by the present invention are shown in Figure 1. It can be seen that when the highly dispersed coated Co3O4 / MoS2 / CC heterostructure self-supporting hydrogen evolution electrode material prepared by the present invention is used for acidic electrochemical hydrogen evolution reaction, it reaches 10 mA cm -2 The overpotential of the current density is only 86.1mV, and the Tafel slope is 104.4mV·dec -1 , and has good electrochemical hydrogen evolution catalytic performance and stability.
[0044] Figure 5 This is the long cycle stability curve of the Co3O4 / MoS2 / CC sample prepared in the present invention. It can be seen that in the 12-hour stability test, the self-supporting composite electrode material exhibits good electrocatalytic hydrogen evolution stability and does not show obvious performance degradation.
[0045] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material, characterized in that The following steps are involved: (1) Cut the conductive carbon cloth, soak it in an alcohol solution, and remove the organic impurities on the surface by ultrasonic treatment. After taking it out, rinse it with water, and then soak it in potassium permanganate solution at room temperature. After taking it out, wash and dry it; (2) 2-Methylimidazole is stirred and dissolved in water to form a solution A; cobalt nitrate hexahydrate is stirred and dissolved in water to form a solution B; after solutions A and B are completely dissolved, solution B is poured into solution A, and the mixture is stirred and mixed evenly, and the carbon cloth dried in step (1) is placed flat in the mixed solution and soaked at a constant temperature; the carbon cloth is taken out, washed, and dried to obtain a cobalt-based MOF-loaded carbon cloth, which is referred to as Co-MOF; (3) immersing the Co-MOF obtained in step (2) in a sodium molybdate dihydrate aqueous solution at a constant temperature, taking it out and washing it with water to remove the unstable substances loaded on the surface, and drying it to obtain CoMoO4 / CC; (4) Place the CoMoO4 / CC prepared in step (3) flatly in a porcelain boat with a lid, place thiourea in the direction of the air inlet, and place CoMoO4 / CC in the direction of the air outlet. Perform constant temperature heat treatment in an Ar gas environment, and the sample obtained by sulfurization is recorded as Co3O4 / MoS2 / CC.
2. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: The alcohol solution in step (1) is any one of ethanol and isopropanol.
3. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 2, characterized in that: The ethanol described in step (1) is 95% ethanol.
4. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: The mass molar concentration of the potassium permanganate solution in step (1) is 0.5 M, and the soaking time is 1-2 hours.
5. The method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: The molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate in step (2) is 8:
1.
6. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: The constant temperature soaking in step (2) refers to soaking at 25°C for 6-8 hours.
7. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: In steps (1) to (3), the washing refers to rinsing with deionized water, and the drying refers to drying at 50° C. for 6-12 hours.
8. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: The concentration of the sodium molybdate dihydrate aqueous solution in step (3) is 2-10 mg / mL; the constant temperature immersion refers to immersion at 25°C for 12-24 hours.
9. A method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: In step (4), the Ar gas flow rate is 50 sccm.
10. The method for preparing a highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material according to claim 1, characterized in that: The constant temperature heat treatment in step (4) refers to heating to 500°C and constant temperature heat treatment at 500°C for 1-2h, with a heating rate of 2-5°C·min -1 .
11. A highly dispersed coated Co3O4 / MoS2 / CC heterostructure hydrogen evolution electrode material prepared according to the method according to any one of claims 1 to 10.
Citation Information
Patent Citations
Bimetallic nitrogen doped carbon / molybdenum disulfide composite electrocatalyst material, preparation method thereof and application thereof
CN109499600A
Co-N / C@MoS2 composite material, preparation method and application in lithium air batteries
CN110649271A